Perlakuan Akuntansi Pajak Pertambahan Nilai Terhadap Pengaruh Laporan Keuangan UD. DEVI - Diwa, Jamaluddin Azhari; Harahap, Hamida; Andri, Shofwan (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2023)
The researcher aims to investigate the accounting treatment of VAT on the influence of financial reports on UD. Devi. Deep understanding of how UD. Devi manages the value added tax aspect and how it is reflected in financial reports will provide valuable insight for business owners, investors, creditors, employees and governments. By understanding this concept, companies can optimize tax management, avoid unintentional tax errors, and ensure compliance with applicable tax regulations. The method applied in this research is a quantitative descriptive method. This approach is carried out by collecting, presenting and analyzing data to form a clear picture regarding the calculation, recording and reporting of value added tax in accordance with the provisions of the applicable tax law. This research provides valuable insight for business owners, investors, creditors, employees and governments regarding the complexity of the relationship between accounting and value added tax in the context of UD. Devi